Multiple ion doping in BiVO4 as an effective strategy of enhancing photoelectrochemical water splitting: A review - Kalanoor, Basanth S.; Seo, Hyungtak; Kalanur, Shankara S. (Materials Science for Energy Technologies, 2021)
Bismuth vanadate (BiVO4) is one of the extensively studied semiconductors in solar water splitting reactions. Due to its inherent properties, much of the utilization of BiVO4 in water splitting is focused on the modified form rather than in native or pure form. Because the pure BiVO4 suffers from numerous limitations and thus structural and chemical modifications are crucial for increasing the solar water splitting efficiency. Primarily, the presence of polarons, low bulk charge transport efficiency, poor water oxidation capability, and stability hinder the water splitting efficiency. The current research developments indicate that the essential modification in BiVO4 via doping is vital and widely implemented for achieving higher photoelectrochemical (PEC) water splitting activity. Recently, the doping strategy in BiVO4 has shifted beyond the single element doping to the co-doping strategy (involving multiple dopants) to further boost the water splitting efficiency that provides extended advantages. In this review, the advancements of co-doping strategies implemented in BiVO4 and their influence on structural, optical, chemical, band edge properties, and stability were summarized. Importantly, future challenges and perspectives are discussed that are beneficial in selecting dopants and designing fabrication strategies to yield highly efficient and optimized BiVO4 for enhanced solar water splitting reactions.
Keywords: Bulk charge; Bulk charge transport; Carrier dynamics; Charge transfer efficiency; Co-doping; Doping strategies; Photoelectrochemical water splitting; Solar water splitting; Water splitting; Water splitting reactions; BiVO4; Bulk charge transport; Carrier dynamics; Charge transfer efficiency; Co-doping